An analysis of the Zimbabwe heads of Christian denominations’ call for a Sabbath on elections - Mujinga, Martin (Stellenbosch Theological Journal, 2023)
The Zimbabwe heads of Christian denominations issued a pastoral letter proposing to postpone the general elections for seven years. The leaders argued that Zimbabwe’s political paralysis and the economic decline have a long history and they needed to be addressed. The leaders called for a national Sabbath on all political contestation to allow for the rebuilding of trust, and confidence, reset politics, and chart a shared way forward toward a comprehensive economic recovery path in a non-competitive political environment. Their views were criticised by politicians and individuals resulting in the Church leaders withdrawing the call. This article was aimed at analysing the church leaders’ theological justification of the Sabbath call. It also challenged the leaders’ muting of their prophetic voices at a time when they were supposed to shout louder on issues that direct political leaders to democratic elections that are controversially marred with mistrust, intimidations, abductions, and rigging.